An Extension of the Blinder-Oaxaca Decomposition to Non-Linear Models - Thomas K. Bauer; Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
In this paper, a general Blinder-Oaxaca decomposition is derived that can also be applied to non-linear models, which allows the differences in a non-linear outcome variable between two groups to be decomposed into a part that is explained by differences in observed characteristics and a part attributable to differences in the estimated coeffcients. Departing from this general model, we show how it can be applied to different models with discrete and limited dependent variables.
Keywords: C20; C13; 330; Blinder-Oaxaca decomposition; non-linear models